DNA Barcoding of the insetivorous bats of Parambikulam tiger reserve western ghats, Kerala - Parvathy Venugopal (Department of Wild life Sciences , College of Forestry, 2013)
The study was carried out at Parambikulam Tiger Reserve during 2012- 2013 with an objective of DNA barcoding the insectivorous bats to unravel the taxonomic ambiguity. The methods employed were the phenol-chloroform extraction (Sambrook et al., 1989) or the GeniPurelM Mammalian Genomic DNA Purification Kit (GeNei™). The sequences were compared with those registered in NeB! databank (blast.ncbi.nlm.nih.gov). The phylogeny reconstruction and the calculation of genetic distances were done using the MEGA 5.0 (Tamura et al., 2011). In this study, three bat species such as Hipposideros speoris, Megederma spasma and Rhinolophus rouxii, were identified using the partial cytochonne b sequence from nine samples of individuals. But the species, Megaderma spasma and Hipposideros speoris showed a genetic distance between two percent and 11 % while compared with the Genbank sequences of those species. Bradly and Baker (2001) considered that a genetic distance more than 10% or between two percent and 11% at cytochrome b is an indication of species level divergence or valid species. So the high sequence divergence in Megaderma spasma and Hipposideros speoris of present study with the same species from South Asia and South India gives an idea on the existence of conspecific population or valid species in these localities. The high sequence divergence may possible as they were collected from two different geographic locations and they result from geographic barriers separating genetic flow. To identify this complexity, the present study recommends additional study concerning specific status and for that more specimens should be collected from each geographical location. Because of this high genetic distance or sequence divergence between the sequences of Megaderma spasma and Hipposideros speoris of present study and that of retrieved from Genbank were clustered as sister clades in their respective phylogenetic neighbour-joining tree. The two sequences of Megaderma spasma,